การศึกษาและวิเคราะห์ฮาร์มอนิกจากการใช้หลอดไดโอดเปล่งแสงสำหรับการประหยัดพลังงานในอาคาร THE STUDY AND ANALYSIS OF HARMONIC FROM USING LIGHT EMITTING DIODE FOR SAVING ENERGY IN BUILDING - บรรจงจิตร ศุลี; พรพจน์รัตนะกุล วินัย (Srinakharinwirot University Journal of Sciences and Technology, 2021)
Nowadays, LEDs are generally employed in both internal and external lighting systems. However, using a light emitting diode in the lighting system may affect the power quality due to the driver operation-converts alternating current (AC), to direct current (DC). This paper presents the measurement and analysis of the power quality of various LED types used in Thailand by using an experimental setup. The experimental studies are divided into three cases: 1. E27 of LED luminaires, 2. Panels of Led luminaires, and 3. Various lamp bases of LED luminaires. In addition, the current harmonic distortion when the LEDs are dimmed and undimmed are compared to the IEC 1000-3-2 and IEC 61000-3-2: 2018 standard. Results show LEDs giving a performance of energy saving and dimming. However, the use of LEDs requires consideration of the harmonic issues, since each type of LEDs different harmonic characteristics depending on the manufacturer.